Strategi Komunikasi Persuasif Guru BK dalam Mengatasi Kenakalan Siswa di SMAN 1 Alas Barat - Sukardi, Mardiki; Rakhmatullah, Vivin Nila (Lembaga Yasin AlSys, 2024)
Delinquency is behavior that violates the norms and rules that apply in the school environment, and also has the potential to disrupt students' learning achievement and welfare at school. Therefore, there is a need for a persuasive communication approach from Guidance and Counseling Teachers to overcome negative student behavior at SMA Negeri 1 Alas Barat. This research aims to determine the persuasive communication strategies of guidance and counseling (BK) teachers in dealing with delinquency among students at SMA Negeri 1 Alas Barat. This research uses a qualitative descriptive method based on primary and secondary data and uses observation, interview and documentation data collection techniques. Data was analyzed interactively using steps, namely data reduction, data presentation and drawing conclusions. The results of this research show that the persuasive communication strategies used by guidance and counseling (BK) teachers in dealing with student delinquency are psychodynamic strategies, sociocultural strategies and the meaning construction strategy. The psychodynamic strategy focuses on emotions, thoughts and personal approaches which enable guidance and counseling teachers to build good relationships with students, the sociocultural strategy emphasizes the importance of involving the student's social and family environment in shaping behavior and the meaning construction strategy which focuses on a deep understanding of the reasons behind delinquent acts.